The impact of lesion length and vessel size on outcomes after sirolimus-eluting stent implantation for in-stent restenosis. Issue 9 (21st November 2007) - Habara, S; Mitsudo, K; Goto, T; Kadota, K; Fujii, S; Yamamoto, H; Kato, H; Takenaka, S; Fuku, Y; Hosogi, S; Hirono, A; Yamamoto, K; et al.
Abstract : Objectives: We evaluated the predictors of recurrent restenosis and the impact of lesion length and vessel size on outcomes in patients treated with routine sirolimus-eluting stent (SES) implantation for in-stent restenosis (ISR) of bare-metal stent (BMS). Methods: In this study, 250 consecutive patients with 275 lesions after SES implantation for ISR of BMS were enrolled. Follow-up angiogram was obtained in 239 patients with 258 lesions eight months after implantation (follow-up rate: 95.6%). We compared characteristics of patients and lesions between the two groups (the recurrent restenosis group and the no-restenosis group). Results: Recurrent restenosis was angiographically documented in 43 lesions (16.7%). Recurrent restenosis was found in 30.4% with small vessel lesions (reference diameter of less than 2.5 mm, 92 lesions) and 23% with the diffuse type lesions (106 lesions). Seventy-two per cent of patients had a focal pattern of recurrent restenosis. Previously recurrent ISR lesions (odds ratio (OR) 1.94, 95% confidence interval (CI) 0.94 to 4.06, p = 0.05), reference diameter of less than 2.5 mm (OR 2.41, CI 1.05 to 5.41, p = 0.03), diffuse type restenosis (OR 4.48, CI 2.12 to 9.94, p = 0.0001) and dialysis patients (OR 4.72, CI 1.42 to 15.7, p = 0.01) were independent predictors of recurrent restenosis. Conclusions: Small vessels, diffuse type restenosis and dialysis patients were still the predictors of recurrent restenosis in patients treated with SES for ISR of BMS.